(untitled) (Castilla. Estudios de Literatura, 2020)
This research paper directly approaches José-miguel Ullán’s haikism as a poetical practice held on a series of specific traditions. With a meaning determined by its use and its different ways to be introduced into the western literature in general, and in Spain in particular, where it was late. Afterwards, we will analyze how this poetical meaning fits inside the Ullán’s aesthetic thought and his other works, where some aspects related to visual arts are introduced. Moreover, we will pay attention on his interest for the hispanic-american Neobaroque’s poetical proposals.